Fast ultrasound-assisted treatment of urine samples for chronopotentiometric stripping determination of mercury at gold film electrodes - Munoz, RAA; Felix, F. S.; Augelli, M. A.; Pavesi, T.; Angnes, L. (Elsevier B.V., 2006)
This work describes an efficient, fast, and reliable analytical methodology for mercury determination in urine samples using stripping chronopotentiometry at gold film electrodes. The samples were sonicated in the presence of concentrated HCl and H2O2 for 15 min in order to disrupt the organic ligands and release the mercury. Thirty samples can be treated over the optimized region of the ultrasonic bath. This sample preparation was enough to allow the accurate stripping chronopotentiometric determination of mercury in the treated samples. No background currents and no passivation of the gold film electrode due to the sample matrix were verified. The samples were also analyzed by cold vapour atomic absorption spectrometry (CV-AAS) and good agreement between the results was verified. The analysis of NIST SRM 2670 (Toxic Metals in Freeze-Dried Urine) also validated the proposed electroanalytical method. Finally, this method was applied for mercury evaluation in urine of workers exposed to hospital waste incinerators. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ultrasound-assisted treatment; ultrasonic bath; stripping chronopotentiometry; mercury; gold film electrode; urine